Challenging the exclusion of immigrant peers. (January 2023) - Palmer, Sally B.; Gönültaş, Seçil; Yüksel, Ayşe Şule; Argyri, Eirini K.; McGuire, Luke; Killen, Melanie; Rutland, Adam
The present study examined age-related differences in bystander reactions within the context of peer exclusion of national ingroup (British) and immigrant outgroup (Australian or Turkish) peers. The immigrant peers were from nations that varied in terms of their perceived intergroup status in Britain. Participants were British children ( n = 110, 8–11 years) and adolescents ( n = 193, 13–16 years) who were presented with one of three scenarios in which a British national, Australian immigrant, or Turkish immigrant peer was excluded by a British peer group. Participants indicated their bystander responses. Perceived similarity and bystander self-efficacy were examined as possible correlates of bystander reactions. Findings revealed that children were more likely to directly challenge the social exclusion when the excluded peer was British or Australian compared with when they were Turkish. In contrast, adolescents did not differentiate in their response—they were equally likely to directly challenge the exclusion regardless of the excluded peer's nationality. Importantly, when the excluded peer was Turkish, moderated mediation analysis showed that, with age, there was higher bystander self-efficacy for challenging the exclusions. In turn, higher bystander self-efficacy was related to higher direct challenging. These novel findings demonstrate the importance of intergroup relations, perceived similarity, and bystander self-efficacy in the emergence of age-related differences in bystander reactions to the exclusion of immigrant peers.